Gender-Relative Effect of Project-Based Learning Method on Academic Achievement and Retention Of Technical College Students in Basic Electricty - Eze, Titus Iloduba; Onwusuru, Ijeoma Madonna; Ginigeme, Onyeka Ogechi (Universitas Ahmad Dahlan, 2021)
The gender-related controversies associated with effects of various teaching methods gave rise to this study. This study was conducted to ascertain the gender-relative effect of project-based learning method on academic achievement and retention of technical college students in Basic Electricity. The study was carried out in Anambra state and the design of the study was quasi-experimental research with pretest, posttest, delayed posttest non-randomized control group design involving students’ intact class groups. A sample of 92 NTC II students was drawn from a population of 179 students of state owned technical colleges in Anambra state. The study was guided by two research questions and two null hypotheses which were tested at 0.05 level of significance. For collection of data, based on the units covered, Basic Electricity Achievement Test (BEAT), a 40-item multiple choice test served as the instrument. Validation of the instrument, as well as the lesson plans for both control and experimental groups were done by three experts from the faculty of education, Nnamdi Azikiwe University Awka. KR-20 was used to determine the reliability coefficient of the instrument which was found to be 0.82. The research questions were answered using mean and standard deviation, while the hypotheses were tested using Analysis of Covariance (ANCOVA). Findings revealed that considering the both genders, students in technical college who were taught Basic electricity using project-based learning method had higher achievement and retention scores than those taught with the conventional teaching method. Also findings revealed that there was no significant difference in the mean achievement and retention scores of the students taught basic electricity using PBLM. Based on the findings of this study, it was concluded that PBLM has the potential to improve male and female technical college students’ academic achievement and retention in Basic electricity. Consequently, it was recommended among others that Basic electricity teachers should use PBLM in the teaching of Basic electricity and grant students equal opportunity during classroom instructions irrespective of gender so as to enhance students’ academic achievement and retention in the subject.